PENGALAMAN WISATAWAN DOMESTIK DI DAYA TARIK WISATA PANTAI PANDAWA: PENGALAMAN WISATAWAN DOMESTIK DI DAYA TARIK WISATA PANTAI PANDAWA - Dewi, Ni Putu Nadia Puspita; Widana, Ida Bagus Gede Agung; Lilasari, Luh Nyoman Tri (Journal of Applied Science in Tourism Destination, 2024)
This The tourist experience is the overall interaction and perception that a person gets during a tour. This study aims to determine the experience of domestic tourists at the pandawa beach tourist attraction which analyzes the Tourist Experience variable through its eight dimensions, namely Comfort, Educational, Hedonic, Novelty, Beauty, Safety, Recognition, and Relational. This research was conducted by taking a sample of 210 domestic tourist respondents. Data collection was carried out by distributing questionnaires through online and offline media. Furthermore, this study uses a quantitative approach with a descriptive analysis method carried out using the SPSS 24 software program. The results showed that the Pandawa Beach Tourism Destination as a whole succeeded in providing a good and satisfying tourist experience for domestic visitors. With an overall average value of 3.86 which is included in the Good category, various aspects of the tourist experience at Pandawa Beach are rated positively. The indicator with the highest score is Beauty with a score of 4.08, indicating that visitors are very impressed with the natural beauty and scenery on this beach.